Pengaruh Etos Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Dengan Motivasi Kerja Sebagai Variabel Intervening Pada SMK Negeri 3 Pariaman - Novita, Sherly; Sari, Marta Widian; Pratiwi, Nila (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The purpose of this study was to find out how much influence work ethic and work discipline have on teacher performance with work motivation as an intervening variable at SMK Negeri 3 Pariaman. Methods of data analysis using a questionnaire, with a sample of 62 respondents. The data analysis method used is SEM. Based on the results of the study, it shows that there is a negative and insignificant influence between work ethic and work motivation. There is a positive and significant influence between Work Discipline on Work Motivation. There is a positive and insignificant influence between work ethic and teacher performance. There is a positive and significant influence between Work Discipline on Teacher Performance. There is a positive and insignificant influence between Work Motivation on Teacher Performance. Work Motivation does not mediate Work Ethics on Teacher Performance. Work Motivation does not mediate Work Discipline on Teacher Performance. The contribution of the work ethic and work discipline variables to teacher performance with work motivation as an intervening variable has an effect of 62.0% while the remaining 38.0% is influenced by other variables outside this study. Based on the results of this study, it is hoped that the SMK Negeri 3 Pariaman can improve teacher performance by increasing the work ethic, work discipline and work motivation through each indicator.